Determinant Factors and Possible Causes Associated with the Success or Failure of Loss of Excess Weight (%Pep) in Patients Submitted to Bariatric Surgery (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: bariatric surgery; weight loss; morbid obesity; physical activity